Diversity and evolution of the highly polymorphic tandem repeat LEI0258 in the chicken MHC-B region - Chazara, O.; Chang, C.-S.; Bruneau, N.; Benabdeljelil, K.; Fotsa, J.-C.; Kayang, B.B.; Loukou, N.E.; Osei-Amponsah, R.; Yapi-Gnaore, V.; Youssao, I.A.K.; Chen, C.-F.; Pinard-Van Der Laan, M.-H.; et al. (Immunogenetics, 2013)
The chicken major histocompatibility complex (MHC) is located on the microchromosome 16 and is described as the most variable region in the genome. The genes of the MHC play a central role in the immune system. Particularly, genes encoding proteins involved in the antigen presentation to T cells. Therefore, describing the genetic polymorphism of this region is crucial in understanding host-pathogen interactions. The tandem repeat LEI0258 is located within the core area of the B region of the chicken MHC (MHC-B region) and its genotypes correlate with serology. This marker was used to provide a picture of the worldwide diversity of the chicken MHC-B region and to categorize chicken MHC haplotypes. More than 1,600 animals from 80 different populations or lines of chickens from Africa, Asia, and Europe, including wild fowl species, were genotyped at the LEI0258 locus. Fifty novel alleles were described after sequencing. The resulting 79 alleles were classified into 12 clusters, based on the SNPs and indels found within the sequences flanking the repeats. Furthermore, hypotheses were formulated on the evolutionary dynamics of the region. This study constitutes the largest variability report for the chicken MHC and establishes a framework for future diversity or association studies. © 2013 Springer-Verlag Berlin Heidelberg.
Keywords: Chicken; Evolution; Gallus gallus; LEI0258; Major histocompatibility complex; MHC